Risk of incisional hernia after laparoscopic colorectal surgery: surgeon’s worries and challenges - Byung Mo Kang (Journal of Minimally Invasive Surgery)
The incidence and risk factors of incisional hernia after laparoscopic surgery for colorectal disease have not yet been fully investigated. The surgeon should always consider several potential risk factors of incisional hernia when closing the abdominal wall in laparoscopic colorectal surgery.